Living and working in ethnic enclaves: Language proficiency of immigrants in US metropolitan areas - Julia Beckhusen; Raymond J. G. M. Florax; Thomas de Graaff; Jacques Poot; Brigitte Waldorf (Institute for the Study of Labor (IZA), 2012)
Learning English is a potentially profitable investment for immigrants in the U.S.: while there are initial costs, the subsequent benefits include the ability to communicate with the majority of the population, potentially leading to better paying jobs and economic success in the new country. These payoffs are lessened if immigrants choose to live and work in ethnic enclaves where the necessity to communicate in English is weak. Ethnic enclaves are widespread and persistent in the U.S. This study uses data from the 2010 American Community Survey to examine the impact of residential and occupational segregation on immigrants' ability to speak English. We allow for heterogeneity in the relationship between segregation and English language proficiency across ethnic groups and focus specifically on Mexican and Chinese immigrants. Our results show that immigrants in the U.S. who live and work among high concentrations of their countrymen are less likely to be proficient in English than those who are less residentially and occupationally segregated. The magnitude of the effect of segregation on language proficiency varies across immigrants' birthplaces and other salient characteristics defining the immigration context.
urn:nbn:de:101:1-201206125780
Keywords: F22; J15; J24; R23; 330; U.S. immigration; language acquisition; ethnic enclaves; residential segregation; occupational segregation; Migranten; Ethnische Gruppe; Segregation; Mehrsprachigkeit; USA